Balancing equity and global health security towards a fair and effective pandemic agreement - Renganathan, Elil; Tediosi, Fabrizio; Abecasis, Ana; Bassat, Quique; Berner-Rodoreda, Astrid; Casamitjana, Núria; Froeschl, Guenter; Kashima, Simone; Placencia, Antoni; Raviglione, Mario Carlo Battista; Rocamora, Alberto; Skordis, Jolene (International journal of public health, 2025)
The COVID-19 pandemic exposed vulnerabilities in health systems and stark inequities between high-and low-income countries in accessing life-saving resources, hindering global control efforts. Recent outbreaks of mpox, Marburg virus disease (MVD) and avian influenza (H5N1) are further reminders of the continuing threat posed by zoonotic diseases. World Health Organization (WHO) Member States agreed in December 2021 to develop a new international instrument for pandemic prevention, preparedness, and response. This agreement aims to strengthen health systems, ensure equitable access to vaccines and treatments, improve supply chains, and foster global collaboration [1.] WHO member state negotiations face barriers, particularly on intellectual property (IP) rights, equitable vaccine distribution, and pathogen sample sharing, with tensions between HICs and LMICs over resource allocation and benefit sharing. Some countries prioritize the amended 2024 International Health Regulations (IHR) as a binding mechanism for pandemic response [2.] However, the IHR lack provisions for fair Pathogen Access and Benefit Sharing (PABS) and a One Health approach, necessitating a distinct pandemic agreement. The slow pace of negotiations has raised concerns about whether a comprehensive agreement will be finalized in time to mitigate the impact of future pandemics [3.] In addition, the recent United States Government decision to withdraw from WHO and to drastically cut development assistance is likely to further threaten successful negotiations and implementation.
Gesehen am 26.11.2025